Mobile edutainment games: road safety for kids - Nur Izdihar, Ab Ghani (2013)
An application that is suits for mobile is commonly developed in order to make the task easier to do and to get something that users needed. Knowledge can be gained through various kinds of way, not to mention games. This application is for Android users. Using Adobe Flash 6 and Adobe Photoshop CS6 as parts of the development tools, this project is about developing a standalone mobile edutainment games which is able to help the kids aged four to six to understand and being exposed to the importance of the road safety. In case the kids are not familiar with the application, parents and teachers can play the role to show how the application will runs. The objectives are to create awareness and to improve the understanding of road safety amongst kids. The existing campaigns through television,. radio and flyers were not so close to the kids. The application starts with the learning session first and then it continues with the games session as the activities to sharpen kids' memory. Few of informal interview sessions regarding road safety awareness had been done in order to get direct feedback from the kids. The application is expected to fulfil the aims and objectives claimed in this project. Kids will be able to be on the road, independently and safely and the number of accidents involving kids will slowly decrease.